Explaining IT Outsourcing Satisfaction using Dombergerâs Theory: An SME Perspective - Yap, Ching-Seng; Lim, Yet-Mee; Lee, Teck-Heang (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2013)
IT outsourcing has emerged as an important tool for enabling organizations to gain access to specific skills and services, focus on their core competencies, and reduce the cost of IT service provision. With the increasing number of IT outsourcing failures, it is timely to identify the determinants of IT outsourcing satisfaction. This study investigates the types of IT function outsourced and examines the factors influencing customer satisfaction in IT outsourcing in Malaysian small- and medium-enterprises. Using an email questionnaire survey, data are collected from 100 firms listed on the Directory of Small and Medium Enterprises in Malaysia. Drawing from Dombergerâs Theory of the Contracting Organization, four hypotheses are developed and tested in this study. Using the PLS path modelling technique, the findings show that focus on core competency, cost reduction, access to IT expertise and skills, and flexibility are positively related to customer satisfaction in IT outsourcing. The paper includes implications and recommendations for future studies.